Hospital costs and unexpected demand: The case of Greece - Zoe Boutsioli (The Open Economics Journal, 2011)
Demand for hospital inpatient care varies in a consistent way. However, a part of this variability is unpredictable. Hospitals react to this situation by holding standby capacity in order to be prepared to meet unanticipated surges in demand. This paper examines the production responses to unexpected hospital demand on a sample of Greek public hospitals over the period 2001-2005. The hospital output is measured by the number of inpatient admissions, distinguishing them into elective and emergency. The unexpected demand is measured as the difference between actual emergency admissions and forecasted emergency admissions using an Autoregressive Moving Average model. The results support the hypothesis that production reactions to unexpected demand have a significant impact on hospital costs.
Keywords: C22; F31; 330; hospital; production; cost; uncertainty; demand; Greece